SELECTING THE SCHEME OF TECHNOLOGICAL CONNECTION OF SUBSCRIBERS TO THE HEAT NETWORK UNDER CONDITIONS OF TRANSITION TO PULSE CIRCULATION OF THE HEATER IN THE EQUIPMENT OF HEAT SUPPLY UNITS - A. N. Makeev (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The aim is to justify the expediency of a transition en masse to independent connection of heat consumption systems  under the conditions of pulse circulation of the coolant through the  equipment of a heat supply unit in order to increase the overall  energy efficiency of district heat supply systems.Methods. The research is based on methodologies for the effective use of technologies providing a means of effecting a pulsed motion  of the coolant in the heat supply system. The advantages and  disadvantages of known technical solutions are identified and  summarised. Hydraulic accumulators or any other devices for  damping a hydraulic shock can be used as devices for preventing the propagation of a wave of hydraulic shock into the transport mainline.Results. An analysis of approaches to heat consumption system  connection is carried out in order to assess power efficiency; the  most effective ways for improving the efficiency of heat and power  devices are identified; a synthesis of the technical solution for the  implementation of a technological connection of heat consumption  systems is performed. The expediency of transition to independent  connection of heat consumption systems under the conditions of  pulse circulation of coolant in heat supply units is demonstrated. The independent scheme of connection of subscribers to the heat network is indicated as the most appropriate. The factors  constraining the en masse transition to independent connection of the heat load are determined. Based on the analysis and scientific  research in the field of increasing the energy efficiency of heat and  power systems, the transition to pulse circulation of the coolant in  the heat supply unit of the independent heat consumption system is  selected. The presented technical solutions are confirmed by Russian Federation patents of inventions and utility models.Conclusion. It is shown that the use of pulse coolant circulation in  the equipment of heat supply units for independent connection of  heat consumption systems will increase the reliability and long-term  operation of the recuperative heat exchanger, as well as increase the overall energy efficiency of the heat supply system.